EVALUASI PERTUMBUHAN STEVIA REBAUDIANA BERT. TETRAPLOID SECARA IN VITRO DAN DI LAPANG UNTUK PRODUKSI STEVIOSIDA DAN REBAUDIOSIDA-A - Adabiyah, Rifatul; Ratnadewi, Diah; Ermayanti, Tri Muji (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTGenetic improvement through tetraploid induction of Stevia rebaudiana is important in order to increase the sweetener content, steviol glycoside. Tetraploid plants of several species after induction with colchicine and oryzalin have higher growth and secondary metabolite contents compared to the diploid plants. This study was aimed to evaluate growth as well as their stevioside and Reb-A content of S. rebaudiana tetraploid and diploid (control) plants cultured in vitro and grown in the field after acclimation process. This study used 3 tetraploid clones, namely B60.3H8, P1T22, P3T5, and 1 diploid clone as control. Shoot tips were cultured on MS medium without addition of plant growth regulators for 6 weeks, then they were acclimated in a greenhouse, followed by planting them in the field. Growth of shoot culture, plantlets in the greenhouse and plants in the field were observed. Analysis of stevioside and Reb-A was done by HPLC. The results showed that plantlets of diploid clone had higher in vitro growth and survival rate in the greenhouse than that of tetraploids. Tetraploid clone P1T22 had similar growth as diploid plants, but higher than the growth of tetraploid B60.3H8 and P3T5. Fresh and dry weights of B60.3H8 was similar with diploid plants, but higher than P1T22 and P3T5 tetraploid clones. The highest level of stevioside and Rebaudiosida-A was found in tetraploid B60.3H8 clone, the lowest was found in the diploid plants. The highest ratio of stevioside : Reb-A was found at B60.3H8 tetraploid clone. Keywords: Stevia rebaudiana, in vitro, field, growth, Stevioside, Rebaudioside-A, tetraploid